Trussmorphometric and meristic characters of kelabau fish (Osteochilus melanopleurus Bleeker, 1852) from three populations in Kampar, Siak, and Rokan Rivers, Riau Province - Nur Asiah; Sukendi Sukendi; Junianto Junianto; Ayi Yustiati; Windarti Windarti (Jurnal Iktiologi Indonesia, 2019)
The purpose of this study was to understand the morphometric and the meristic characters of the kelabau fish from the Siak, Kampar, and Rokan river populations that could be used as an initial step forconservation. A total of 113 kelabau from Kampar River, 58 fish from the Siak River and84 fishfrom the Rokan River was used in this study. Measurement of 21 morphological characters was conducted using a morphometric truss method. The analysis was carried out using a one-way ANOVA and Discriminant Function Analysis ( SPSS software). Meristiccharacteristics were analyzed descriptively for 30 fish per population. Results indicates that among 21 morphometrical characteristics, 19 characters shown a significant different (P <0.05) and 2 characters were not significantly different (P> 0.05). This result indicates that fish population from all sampling areas shown similar characteristics. The discriminant analysis results show that the specific characters of the O. melanopleurus were A5, A2, A6, B1and D4. Scatterplot results indicate that the Rokan River population was separate from the Siak and Kampar River populations, and the morphology of the fish from the Rokan River population was slightly different from those of the Siak and Kampar River population. The meristic characteristics of fish obtained from all sampling areas were relatively similar. Abstrak Penelitian ini bertujuan untuk memperoleh informasi karakter morfometrik dan meristik ikan kelabau dari Sungai Kampar (Desa Pelalawan), Sungai Siak (Desa Kota Garo Kecematan Tapung Hilir), dan Sungai Rokan (Desa Sekapas Dusun Kualu Angau) yang dapat digunakan sebagai langkah awal konservasi. Sebanyak 113 sampel ikan kelabau dari Sungai Kampar, 58 ikan dari Sungai Siak, dan 84 ikan dari Sungai Rokan digunakan dalam penelitian ini. Pengukuran 21 karakter morfologi dengan metode truss morfometrik. Analisis dilakukan dengan Analisis Varian Satu Arah (ANOVA) dan Analisis Fungsi Diskriminan (DFA) dengan perangkat lunak SPSS.. Karakter meristik dianalisis secara deskriptif pada 30 sampel setiap populasi. Hasil uji signifikansi terhadap 21 karakter yang diuji, 19 karakter berbeda nyata (P<0,05) dan 2 karakter yang tidak berbeda nyata (P>0,05), mengindikasikan semua populasi memiliki karakter yang sama. Hasil analisis diskriminan menunjukkan karakter yang menjadi pembeda A5, A2, A6, B1, dan D4. Berdasarkan fungsi persebaran yang mengelompokkan populasi Rokan terpisah dari Siak dan Kampar, dapat disimpulkan bahwa karakter morfometrik populasi ikan kelabau di Sungai Rokan berbeda. Sebaliknya populasi ikan kelabau di Sungai Siak dan Kampar memiliki karakter yang sama. Karakter meristik tiga populasi Sungai Siak, Kampar dan Rokan relatif sama.